Intrinsic plasmarons in warm graphene. (12th September 2017) - Liu, Daqing; Chen, Shuyue; Zhang, Shengli; Ma, Ning
Abstract: Based on a self-consistent method, we predict theoretically that there exist intrinsic plasmarons in graphene at nonzero temperature, with a well defined mode, as shown by the result of Landau damping. We find that there are sharp differences between the discussed system and the QCD/QED system. Firstly, the thermal mass is proportional to α g 3 / 4 T but not α g T . Secondly, at 0 < q < q c, the fermion channel and plasmaron channel are nearly degenerate, and furthermore the energy difference between fermion and plasmaron becomes larger and larger with increasing q in the region q > q c . Thirdly, the fermion behaves as a 'relativistic particle' with nonzero mass, and the plasmaron exhibits an abnormal dispersion at moderate momentum.